Irish missionaries: from the golden age to the 20th century - Keaney, Marian (Veritas Publications, 1985)
Irish Missionaries is a facinating description of the careers of St. Columbanus and St. Colmcille, the many travels of St. Brendan the Navigator and the life of St. Malachy O Morgair and his links with the Continent. There is also a short biography of St. Oliver Plunkett with a detailed account of the events leading to his execution. The final chapter provides a history of the Benedictine Order of nuns which eventually steeled at Kylemore Abbey, Co. Galway